Effectiveness of Parent Empowerment Program on Parental Self-Efficacy and Quality of Life in Children with: A Quasi-Experimental Study - Hermanto; Sri Nurlian; Haslina; Budi Prasetyo (PT. Nasyah Medika Care, 2026)
Background: Parents of children with long-term health conditions often experience substantial caregiving demands that may affect their confidence and their children’s quality of life. Parent empowerment is considered an important family-centred strategy to strengthen caregiving capacity and improve child well-being. Research Objective: This study aimed to determine the effectiveness of a Parent Empowerment Program in improving parental self-efficacy and quality of life among children with long-term health conditions in Baubau City, Southeast Sulawesi, Indonesia. Methods: A quantitative quasi-experimental study with a pretest–posttest control group design was conducted among 40 parents selected using purposive sampling. Participants were divided equally into intervention and control groups. The intervention group received a structured Parent Empowerment Program, while the control group received routine care. Data were analysed using paired-samples and independent-samples t-tests with a significance level of p<0.05. Results: Parental self-efficacy in the intervention group increased from 58.40±7.12 to 76.85±6.34 (p<0.001), while children’s quality-of-life scores increased from 61.75±8.21 to 78.30±7.46 (p<0.001). Improvements in both outcomes were significantly greater in the intervention group than in the control group. Conclusion: The Parent Empowerment Program was effective in improving parental self-efficacy and children’s quality of life. Integrating structured parental empowerment into paediatric and community health services is recommended to strengthen family-centred care.